An evaluation on cropping system of rice and corn in dry land during dry season - Zainal Arifin; Amik Krismawati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2020)
Dry land has wide and diverse agroecosystem, which potential as growth source to produce dietary crops (foodstuff). The objective of the research was to study the appropriate managerial technique of cropping system for rice and corn to increase production and income of the farm operation in dry land during dry season. The research was conducted on dry land during dry season (DS) I in 2018 at Jatisari Village, Arjasa Subdistrict, Situbondo Regency, on the area of 10,000 m2 width. The research used Randomized Block Design with 4 treatments and 6 replications, includes : (a) Upland rice (20 cm x 20 cm), (b) Upland rice largo super (40 cm x 20 cm x 10 cm), (c) Upland rice largo super (40 cm x 20 cm x 10 cm) + corn (160 cm x 40 cm), and (d) Corn (75 cm x 20 cm). Results of the research showed that the intercropping system between upland rice largo super and corn produced higher yield, 8,151 kg/ha DGH and 2,092 kg/ha grains of corn. Besides that, yield of corn trimming was 2,446 kg/ha fresh biomass. The increase production of intercropping upland rice largo super with corn has increase income of the farmers, IDR. 41,923,100 with R/C ratio 3.25, so that it is economically feasible.